Atmospheric composition of exoplanets based on the thermal escape of gases and implications for habitability. (30th September 2020) - Konatham, Samuel; Martin-Torres, Javier; Zorzano, Maria-Paz
Abstract : The detection of habitable exoplanets is an exciting scientific and technical challenge. Owing to the current and most likely long-lasting impossibility of performing in situ exploration of exoplanets, their study and hypotheses regarding their capability to host life will be based on the restricted low-resolution spatial and spectral information of their atmospheres. On the other hand, with the advent of the upcoming exoplanet survey missions and technological improvements, there is a need for preliminary discrimination that can prioritize potential candidates within the fast-growing list of exoplanets. Here we estimate, for the first time and using the kinetic theory of gases, a list of the possible atmospheric species that can be retained in the atmospheres of the known exoplanets. We conclude that, based on our current knowledge of the detected exoplanets, 45 of them are good candidates for habitability studies. These exoplanets could have Earth-like atmospheres and should be able to maintain stable liquid water. Our results suggest that the current definition of a habitable zone around a star should be revisited and that the capacity of the planet to host an Earth-like atmosphere to support the stability of liquid water should be added.